Pemberdayaan alumni terhadap peningkatan mutu sumber daya manusia di pesantren Al Binaa - Asep Dawami (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2022)
Empowerment has an important role in educational institutions that make a real contribution to the improvement of human resources. Graduates as one of the school's stakeholders have no small contribution to the school starting from; management, improvement of human resources, leadership, and organizational systems. This includes the empowerment of Al Binaa Islamic Boarding School graduates in improving the quality of human resources. This study aims to find out in-depth about the empowerment of alumni in improving the quality of human resources at Al Binaa Islamic Boarding School. This study uses descriptive qualitative methods with data collection techniques in the form of observations, questionnaires, interviews, and documentation from Al Binaa Islamic Boarding School graduates who have done service. The source of this research is research in the field using primary and secondary sources. The results of this study indicate the definition and empowerment of Al Binaa Islamic Boarding School graduates. Empowerment of alumni who can improve the quality of human resources at Al Binaa Islamic Boarding School through a management function approach by taking into account potential strengths and weaknesses.AbstrakPemberdayaan memiliki peranan penting dalam lembaga pendidikan yang memberikan kontribusi nyata terhadap peningkatan sumber daya manusia. Alumni sebagai salah satu stakeholders sekolah memiliki kontribusi yang tidak kecil terhadap sekolah mulai dari: pengelolaan, peningkatan sumber daya manusia, sistem kepemimpinan dan organisasi. Termasuk di dalamnya adalah pemberdayaan alumni Pesantren Al Binaa dalam peningkatan mutu sumber daya manusia. Penelitian ini bertujuan untuk mengetahui secara mendalam tentang pemberdayaan alumni dalam peningkatan mutu sumber daya manusia di Pesantren Al Binaa. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, kuesioner, wawancara, dokumentasi dari alumni Pesantren Al Binaa yang sudah melakukan pengabdian. Sumber penelitian ini adalah penelitian di lapangan dengan menggunakan sumber primer dan sekunder. Hasil dari penelitian ini menunjukkan definisi dan pemberdayaan alumni Pesantren Al Binaa. Pemberdayaan alumni yang dapat meningkatkan mutu sumber daya manusia di Pesantren Al Binaa melalui pendekatan fungsi manajemen dengan memperhatikan potensi faktor kekuatan dan kelemahan.